Diagnosis of wild populations of crazy zucchini in the Central Highlands of Mexico - Gómez González, Adrián; Rangel Guerrero, Juan Manuel; Morales Flores, Francisco; Aquino Pérez, Gildardo; Santana García, Mario Arturo; Silos Espino, Héctor (Revista Mexicana de Ciencias Agrícolas, 2019)
The species, Cucurbita foetidissima Kunth (crazy zucchini) grows in places that are not conducive to agriculture and has an agro-industrial importance, therefore, it is necessary to know its current situation to propose in the future if the plant is used sustainably. Therefore, morphological variables (foliage and root) of populations located in the region between the states of San Luis Potosí, Jalisco and Zacatecas were analyzed. The plants of La Cocona and Yoliatl San Luis Potosí, contain more guides per plant (9-12), better root attributes, by weight (2536 g), number of guides (67) and volume (2411.2 cm3) and higher fruit content. The Guadalupe and Ojocaliente, Zacatecas plants showed greater length of guides (16-27), length of the petiole (7.5 to 12 cm) and larger leaves (13.5 to 18 cm). With respect to the Chinampas Ojuelos, Encarnación de Díaz and Lagos de Moreno, Jalisco plants, these had a root weight of 1615 g, 33.8 cm perimeter, 10.8 cm wide, 52.6 cm long, 44.5 guides, 1690.5 cm3 in volume and 162 fruits. These low attributes may be due to the fact that the plants were located in sites characterized by warmer climates and with greater precipitation (473.5-573.2 mm) compared to the other regions. In this work, geo-referencing and the size of wild crazy zucchini plants were established as a first strategy to know their habitat status, define a conservation/propagation alternative and propose a sustainable use method according to their agroindustrial potential that is known.
Keywords: Cucurbita foetidissima Kunth; botanical description; characterization; multivariate statistics